Pregnant behind the veil - Grayson, Emmy (Harlequin presents, 2025)
"Alessandra. I could have destroyed my hard-won legal career with one indulgent encounter. My anonymous lover was Michail Sullivan, the illegitimate son of my most hated client. Not only do I have to disclose the shocking terms of his late father's will to him, but also reveal I'm pregnant! Michail. Alessandra Wright will marry me to secure my inheritance and my legacy. Still, I've seen how ruinous passion can be, so our union will be strictly on paper. Until Alessandra walks down the aisle and the air between us crackles with insatiable desire."-- Back cover.